Exploring the relationship between trauma, mental health, and occupational performance in health science center students - Ahmad, Feddah M.; Sajit, Dina M. (Frontiers in Public Health, 2024)
IntroductionAttending university marks a pivotal yet stressful phase in students’ lives, characterized by significant adjustments to a new environment that can impact mental, emotional, and physical well-being. The journey through the acceptance and admissions process into university introduces substantial challenges, academic performance and changes to daily life. Such challenges and corresponding conditions can be intensified for students entering university with prior traumatic experiences.ObjectiveThe purpose the study is: (a) to clarify the factors affecting student mental health by cataloging the prevalence and types of traumatic events (including PTSD and complex PTSD) that students experience, and (b) examine the relationship between students’ mental health and occupational performance through the assessment of satisfaction with daily activities and quality of life (QoL).MethodThe research study utilized a descriptive cross-sectional design. Participants included students pursuing degrees in Medicine, Dentistry, Pharmacy, and Allied Health, (N = 223). Four self-administered questionnaires were employed: the International Trauma Questionnaire (ITQ), Beck’s Depression Inventory (BDI), the Self-Satisfaction of Daily Occupation (SDO), and World Health Organization Quality of Life Brief (WHOQoLBrief). Data was analyzed using descriptive statistics, and Spearman correlation.ResultResults from ITQ revealed participants experienced highest indicators of trauma were 68% affective dysregulation, and 65%, in avoidance and self-organization. Significant negative correlations were found between BDI scores and the quality-of-life social domain and quality of life environment domain (p = 0.001). Regarding BDI scores highest at 23.3% (n = 52) of students reported mild mood disturbance. SDO indicated that satisfaction levels increased with medium activity levels but decreased with high activity levels. In addition, a negative correlation was also found between SDO and BDI scores. Furthermore, a positive correlation between satisfaction with daily occupation (activity level) and WHOQoLBrief both physical, p > 0.001 and psychological, p = 0.006 was identified.ConclusionThis research investigates the cyclical impact of mental health on students’ daily activities, QoL, and occupational performance, particularly among those in Health Sciences Center. The study highlights how traumatic events and poor mental health contribute to dissatisfaction with daily tasks, which in turn leads to a decline in QoL and occupational performance emphasizing the importance of developing effective outreach strategies community.